Sustainability of the Soil Resource in Intensive Production with Organic Contributions - Francia Deyanira Gaytán Martínez; Edgar Vladimir Gutiérrez Castorena; Vicente Vidal Encinia Uribe; Rigoberto Eustacio Vázquez Alvarado; Emilio Olivares Sáenz; Ma. del Carmen Gutiérrez Castorena (Agronomy, 2021)
Organic agriculture is considered an alternative to sustainably preserve soil fertility. For 10 years, ongoing management with organic contributions was carried out in calcareous soil to support or increase fertility by applying 4 t ha−1 of solid poultry manure to produce organic Nopal Verdura (Opuntia Ficus-Indica). In addition, during the 2018 cycle, corn was established as an alternative to diversify agricultural production; the crop was monitored by measuring agronomic variables and the normalized differential vegetation index to evaluate the development of different doses of organic inputs with poultry manure, foliar applications with biofertilizers, or in the irrigation system. The soil physical and chemical analysis was carried out from 2015 to 2020 to monitor nitrogen, phosphorus, potassium, calcium, magnesium, and organic matter before planting and after harvest. The results indicated an increase in nitrogen (>50%), calcium (>130%), and magnesium (>20%), while there was a decrease in phosphorus (50%), potassium (60%), and organic matter (18%). The agronomic management caused an increment of EC in the horizon Ap until 12.93 dS m−1 at the end of each cycle due to the high ambient temperatures recorded and the inadequate irrigation water quality. We did not find significant differences (p > 0.05) in agronomic variables of corn with diverse contributions to organic. However, we obtained a maximum corn yield of 3.9 t ha−1 and nopal production of 143 t ha−1, despite problems of salinity in the horizons Ap during the agricultural cycle. Overall, processed poultry manure is a sustainable source of macroelements for the production of organic crops in calcisols; however, it is necessary to focus on and counteract potassium depletion and the increase in EC through appropriate agronomic management, with organic contributions, both solid and liquid, to increase or sustain production.